Bronchial asthma - what should every doctor know? - Michał Tobiasz; Agnieszka Turkosz; Maciej Tobiasz; Paweł Polski; Rafał Wójcik (Kazimierz Wielki University, 2019)
More than 235 million people worldwide suffer from asthma. Most of the patients have mild asthma, but in a large part of them asthma is not fully controlled and they are exposed to the occurrence of exacerbations. It is believed that the most important reason for poor asthma control is the patients' failure to comply with chronic treatment recommendations. This article describes the symptoms and course of the disease. There is also contain information about the criteria of diagnosis and changes in therapeutic progress which were announced in 2019 by Global Organization for Asthma.